Virtual Ziggurats: Orientalist Views and Playful Spaces - Politopulos, Arēs ca. 20./21. Jh. (Near Eastern archaeology, 2021)
With this quotation, this fifth-century BCE Greek historian provides us with a vivid description of Etemenanki, the ziggurat of Babylon. The ziggurat is one of the most enduring symbols of the ancient Near East: From paintings to movies to books to video games, versions of the stepped constructions emerge in popular culture and imagination all the way from classical Greece until today. One could even argue that the ziggurat is a transhistorical symbol (Crowther 2002); it has existed as a symbol not only produced by and related to the ancient Near East, but has transcended its original historical context and has acquired new meanings and images over time. In this article, I explore this transhistoricity of the ziggurat by examining it within western, modern, popular imagination, and particularly within the context of video games. For this, I take an art-historical approach, examining ziggurats from various games to create a ziggurat typology as portrayed in video games. In doing that, I explore how modern conceptions of the ziggurat affect and shape our understanding of the Near East, and how this can be tied to Edward Said’s concept of orientalism (see also Mol and Politopoulos in this issue). I conclude with a brief discussion on how we can reframe the ziggurat within popular culture in order to increase knowledge and awareness about the history and cultures of the ancient Near East today.